Measuring Zakat Literacy Index : The First Step of Poverty Reduction Efforts - Vima Tista Putriana; Ghina Armya Ginting; Silvy Astari; Yurniwati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Andalas, 2024)
No poverty is one of the Sustainable Development Goals (SDGs) agenda to be achieved by 2030. One of instruments that can be used to solve the poverty in Muslims Communities is zakat. Zakah is an Islamic social and financial tool to help the zakah recipients. This research aims to measure literacy of a Muslim society concerning zakat. The zakat literacy was measured using a technique developed by the Indonesian National Zakat Board in 2019. By applying convenience sampling technique, 115 respondents participated in the survey. Respondents originated from Padang filled up the questionnaires by using social media (Whatsapp groups). Data were analysed using statistical analysis tools. The Zakat Literacy Index (ZLI) was categorized as ‘medium’ level. Concerning the timing of paying zakat, Muslims in Padang preferred to pay zakat during the holy month of Ramadhan. Giving the zakat directly to the individual recipients was preferred than channeling it through formal zakat institutions. When distributing zakat through zakat institutions, accessibility was the most important consideration. The main source of knowledge about zakat was lectures delivered by the Islamic scholars. The finding of this study contributed to the first attempts of building of baseline data of Zakat Literacy Index in Indonesia at the city level. The information revealed from this study can be used by local zakat institutions to plan strategies on how to increase the awareness of public on zakat which at the same time zakat payment will increase. The result of this study also provides baseline for future study.